The Effect Of Special Exercises In Repetitive Training Method On The Development Of Reaction Speed Of U17 Football Players - Temar , Mohamed el Amine; Saci , Abdel Aziz (Journal of Sport Science Technology and Physical Activities, 2021)
The study aims to identify the effectiveness of special exercises in the repetitive training method in developing the reaction speed of football players under the age of 17. For this purpose, we used the empirical method on a sample of 20 players from the abnaa Titteri team, divided into two groups: experimental and controlled groups. The participants were chosen in an intentional manner. The researchers used the Nelson test to collect data. After collecting the findings and processing them statistically, there were statistically significant differences for the pre-post tests of the experimental group and in favor of the post test. On this basis, the study recommended that trainers must be interested in developing the speed of reaction with the use of advanced devices to achieve that.